The Composition of Arthropods in Nipah Fronds Decomposition at Sungai Kakap Mangrove Area in the West Kalimantan - Lastyanti Mulyani; Junardi; Rikhsan Kurniatuhadi (Jurnal Biologi Tropis, 2023)
Anthropogenic activities in Nypa palm (Nypa fructicans) forests directly leave a lot of residual nipa fronds, which take longer to decompose. The decomposition process involves decomposer organisms, one of which is Arthropods. Nevertheless, information regarding the composition of decomposition fronds is still limited. This study aims to obtain data and information regarding the composition of Arthropods and their relationship to the decomposition period. Arthropod sampling was carried out by hand collecting methods at 15, 25, 35, and 45 days after placement. The laying of the nipa palm fronds was determined randomly with a vertical position at 20 cm above the ground surface. Arthropod eggs, larvae, pupae, and imago samples were sorted and preserved in 70% Alcohol. Arthropod data obtained were analyzed descriptively. The results showed that the composition of Arthropods consisted of the class Crustacea and Insecta, each with one order (2 genera) and six orders (32 genera). The orders Diptera (Psychoda, Eristalinus) and Amphipoda (Allorchestoides) were dominant. The average number of individuals found increases with the decomposition period. The role of different arthropods influences their composition in the decomposition process of the nipa palm fronds. It is necessary to study the composition of microbes in each decomposition period.